First Observations of Cirrus Clouds Using the UZ Mie Lidar over uMhlathuze City, South Africa - Nkanyiso Mbatha; Lerato Shikwambana (Applied Sciences, 2022)
Clouds cover more than two-thirds of the earth’s surface and play a dominant role in the energy and water cycle of our planet. Cirrus clouds are high-level clouds composed mostly of ice crystals and affect the earth’s radiation allocation mainly by absorbing outgoing longwave radiation and by reflecting solar radiation. This study presents the characterization of cirrus clouds observed on 10 and 11 April 2019 using the ground-based University of Zululand (UZ) light detection and ranging (lidar) for the first time. Dense cirrus clouds with an average thickness of ~1.5 km at a height range of 9.5–12 km on 10 and 11 April 2019 were observed by the UZ lidar. The UZ lidar observation on 10 April 2019 agreed with the Cloud–Aerosol Lidar with Orthogonal Polarization (CALIOP) observation.